2018
DOI: 10.18632/oncotarget.25294
|View full text |Cite
|
Sign up to set email alerts
|

MAP4K4 controlled integrin β1 activation and c-Met endocytosis are associated with invasive behavior of medulloblastoma cells

Abstract: Local tissue infiltration of Medulloblastoma (MB) tumor cells precedes metastatic disease but little is still known about intrinsic regulation of migration and invasion in these cells.We found that MAP4K4, a pro-migratory Ser/Thr kinase, is overexpressed in 30% of primary MB tumors and that increased expression is particularly associated with the frequently metastatic SHH β subtype. MAP4K4 is a driver of migration and invasion downstream of c-Met, which is transcriptionally up-regulated in SHH MB. Consistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(78 citation statements)
references
References 51 publications
11
66
0
1
Order By: Relevance
“…This is most likely due to dasatinib inhibition of SRC family kinases, which are necessary for focal adhesion formation and turnover [36] . Similarly, dasatinib treatment of cells invading collagen I gels, a soft matrix triggering mesenchymal, integrin-dependent migration of DAOY cells [40] , caused de-adhesion and cell rounding in other human tumor cells [36] . The process of migration associated with cell rounding and blebbing in response to de-adhesion and repression of pericellular proteolytic activity was referred to as mesenchymal to amoeboid transition (MAT) [41] , [42] .…”
Section: Discussionmentioning
confidence: 99%
“…This is most likely due to dasatinib inhibition of SRC family kinases, which are necessary for focal adhesion formation and turnover [36] . Similarly, dasatinib treatment of cells invading collagen I gels, a soft matrix triggering mesenchymal, integrin-dependent migration of DAOY cells [40] , caused de-adhesion and cell rounding in other human tumor cells [36] . The process of migration associated with cell rounding and blebbing in response to de-adhesion and repression of pericellular proteolytic activity was referred to as mesenchymal to amoeboid transition (MAT) [41] , [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested the importance of MAP4K4 in migration. Recently, MAP4K4 expression was shown to be increased in 30% of primary medulloblastoma tumors, particularly in the metastatic SHH β subtype, and was shown to promote the migratory and invasive behavior of medulloblastoma tumor cells 33 . A small interfering RNA screen for modulators of tumor cell motility in an ovarian cancer line identified MAP4K4 as a pro-migratory kinase 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Parallel activation of FGFR and SHH signaling partially phenocopies SMO inhibition by LDE225 and reduces invasion. LDE225 treatment can repress phosphorylation of focal adhesion kinase (FAK) and paxillin [22,23], two molecules critically implicated in integrin-dependent motility and invasiveness in numerous cancers, including MB [24]. SHH signaling promotes epithelial to mesenchymal transition (EMT) and lymph node invasion in bladder cancer [25,26] and hypoxia-induced up-regulation of cancer stem cell genes and EMT in cholangiocarcinoma [27].…”
Section: Discussionmentioning
confidence: 99%